Studi Komparatif Makna Kasb dalam Quran dan Hadits Perspektif Etos Kerja Max Weber - Ahmad Lukman Nugraha; Ahmad Hasan Ridwan (Multidisciplinary Journal of Contemporary Islamic Discourse, 2026)
This paper explores the concept of al-kasb (human effort) in the Qur'an and Hadith, with the aim of analyzing its semantic dimensions and comparing it with Max Weber's theory of work ethic, particularly the notion of a divine "calling" (Beruf). The study employs a qualitative method using a library research design and applies a comparative approach to examine both Islamic and sociological perspectives. The novelty of this paper lies in its interdisciplinary analysis, integrating Islamic theological insights with Western sociological theories to uncover shared ethical motivations underlying work behavior. The findings indicate that the term al-kasb in the Qur’an carries four primary meanings: (1) human action in general, (2) good deeds, (3) bad deeds, and (4) efforts to earn a living. In Hadith, al-kasb is primarily understood as the lawful pursuit of sustenance. A comparative analysis reveals conceptual parallels between al-kasb and Weber’s idea of work as a divine calling, particularly in how both promote diligence and responsibility in occupational life as a form of religious devotion. However, fundamental differences are also identified, including (1) the theological origins of each concept, (2) the development and contextual background of the theories, and (3) the socio-economic impacts of each worldview. The study implies that understanding religious perspectives on work can contribute to developing a more ethically driven workforce, especially in faith-based societies. It also opens further dialogue between Islamic ethical constructs and Western social theories in shaping modern work ethics.